2019
DOI: 10.5194/bg-16-135-2019
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical response of the Mediterranean Sea to the transient SRES-A2 climate change scenario

Abstract: Abstract. The Mediterranean region is a climate change hotspot. Increasing greenhouse gas emissions are projected to lead to a substantial warming of the Mediterranean Sea as well as major changes in its circulation, but the subsequent effects of such changes on marine biogeochemistry are poorly understood. Here, our aim is to investigate how climate change will affect nutrient concentrations and biological productivity in the Mediterranean Sea. To do so, we perform transient simulations with the coupled high-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 85 publications
(148 reference statements)
8
67
1
Order By: Relevance
“…This is consistent with the study of Herrmann et al (2014) who obtained no significant change in phytoplankton biomass, but significant increase in zooplankton biomass and primary production in the north-western Mediterranean Sea where a weakening of deep convection was projected under the SRES A2 scenario. This evolution is, however, in contrast to that simulated by Richon et al (2019) with a decline in zooplankton biomass for the 21st century in the whole Mediterranean basin, under the SRES A2 scenario. The discrepancies of Eco3M-S results with the latter study may be partly explained by differences in nutrient supply at the Gibraltar Strait.…”
Section: Advances Limits and Perspectivescontrasting
confidence: 85%
See 1 more Smart Citation
“…This is consistent with the study of Herrmann et al (2014) who obtained no significant change in phytoplankton biomass, but significant increase in zooplankton biomass and primary production in the north-western Mediterranean Sea where a weakening of deep convection was projected under the SRES A2 scenario. This evolution is, however, in contrast to that simulated by Richon et al (2019) with a decline in zooplankton biomass for the 21st century in the whole Mediterranean basin, under the SRES A2 scenario. The discrepancies of Eco3M-S results with the latter study may be partly explained by differences in nutrient supply at the Gibraltar Strait.…”
Section: Advances Limits and Perspectivescontrasting
confidence: 85%
“…Many studies have already shown, assessed or modeled potential impacts of climate change on Mediterranean marine ecosystems (Galil, 2000;Giorgi and Lionello, 2008;Lejeusne et al, 2010;Albouy et al, 2013;Cramer et al, 2018). Most of them focused on a specific compartment, whether biotic (e.g., Ben Rais Lasram et al, 2010;Benedetti et al, 2018) or abiotic (e.g., Richon et al, 2019). Most of them were conducted at local scales, at the scale of the continental shelf (e.g., Albouy et al, 2014;Hattab et al, 2014) or for specific ecosystems (e.g., Libralato et al, 2015;Corrales et al, 2018).…”
Section: Advances Limits and Perspectivesmentioning
confidence: 99%
“…The red area represents spread in the CMEMS-BIO data as measured by RMSD the basin, whose existence was pointed out in previous studies (e.g. Crise et al 1999, Manca et al 2004, Richon et al 2018a,b, 2019, Di Biagio et al 2019, Reale et al 2020. Relative high values of PO 4 are found in the Alboran Sea and Gulf of Lions (Crise et al 1999, Manca et al 2004, Richon et al 2018a,b, Di Biagio et al 2019, Reale et al 2020, while relatively low PO 4 val-ues are found in the Southern Adriatic, Northern Ionian, Aegean Sea and the Rhodes Gyre.…”
Section: Methodsmentioning
confidence: 57%
“…From a biogeochemical point of view, the Mediterranean Sea is considered an oligotrophic basin with low annual primary production (Sournia 1973, Azov 1991, Robarts et al 1996, Moutin & Raimbault 2002, Siokou-Frangou et al 2010, Lazzari et al 2012, Di Biagio et al 2019, Reale et al 2020 and a negative west− east trophic gradient in productivity and nutrient availability, namely nitrate (NO 3 ) and phosphate (PO 4 ) (Crise et al 1999, D'Ortenzio & Ribera d'Alcalà 2009, Lazzari et al 2012, Richon et al 2018a,b, 2019, Di Biagio et al 2019, Reale et al 2020. The cause of this oligotrophy is ascribed to the relative nutrient-depleted Atlantic water entering the Strait of Gibraltar and undergoing a further depletion of nutrients while moving eastwards across the basin.…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
“…To our knowledge, only a few studies have investigated the effects of climate change on the biogeochemistry of the whole MS with a 3D coupled hydrodynamic/biogeochemical model. Most of those studies, except Moullec et al (2019), have predicted a decline in primary production for the Western Basin and nutrient inputs to the upper layers due to a reduction in vertical mixing (Macias et al, 2015;Richon et al, 2019). Some studies also highlight a reduction of the phytoplankton biomass (mostly for diatoms) (Lazzari et al, 2014;Richon et al, 2019), while Moullec et al (2019) show an increase in phytoplankton biomass.…”
Section: Introductionmentioning
confidence: 99%